A literature review on sustainability of bio-based and biodegradable Plastics: Challenges and opportunities - Moshoodye, Taofeeq Duroja; Nawanir, Gusman; Fatimah, Mahmud; Fazeeda, Mohamad; Mohd Hanafiah, Ahmad; Airin, Abdul Ghani (Tech Science Press, 2022)
This study examines the literature on bio-based and biodegradable plastics published between 2000 and 2021 and provides insights and research suggestions for the future. The study gathers data from the Scopus and ISI Web of Science databases, then picks 1042 publications objectively and analyses their metadata. Furthermore, 144 papers from the Web of Science are analysed to present insights and classifications of the literature based on content analyses, including assessment/evaluation of the sustainability of bio-based and biodegradable Plastics, sustainability of biodegradable Plastics, and factors driving the uptake of biodegradable plastics. The study finds that most research on bio-based and biodegradable plastic film evaluations considered only one dimension of sustainability, few considered two dimensions, and very few considered three dimensions. Though, in recent years, academic and industrial interest has grown dramatically in biodegradable plastics towards sustainability. The triple bottom line method in this report (economic benefit, social responsibility, and environmental protection) was employed to assess the biodegradable plastics towards sustainability. Top journals, Influential authors, top contributing institutions, top contributing nations, and contributions by fields are all identified in this study. This research gives a detailed but straightforward theoretical design of bio-based and biodegradable polymers. The study’s results and future research initiatives provide a new path for further investigation and contribution to the field.